Relevance of Digital Literacy on Undergraduates Knowledge of Educational Research in Lagos State - AREMU, Victoria Iyabo; UDOFIA, Imoh Godwin; OKUNTADE, Japhet Omolere (Ilorin Journal of Education, 2024)
Undergraduates most times find it difficult to execute research exercises successfully due to their inability to acquire the required knowledge needed for that exercise, hence the rationale for this study. Descriptive survey type of research design was adopted for this study. The population for this study comprised of all undergraduates in Lagos State while the target population was all second year students of Adeniran Ogunsanya College of Education, Ijanikin, Lagos State. Multi-stage sampling technique was used to select the sample size for this study. Simple random sampling technique was used by the researchers to select twenty-eight (28) students each from the ten (10) departments selected for this study. A total of two hundred and eighty (280) students form sample size for this study. A self structured instrument titled, “Questionnaire on Relevance of Digital Literacy on Undergraduates Knowledge of Educational Research (QRDLUKER)” containing 20-items on 4-Likert Scale type was designed. The instrument was validated for content and face validity by experts in educational research. With the use of Cronbach Alpha reliability estimate, r-coefficient of 0.819 was obtained. Pearson Product Moment Correlation and Regression analysis were used to analyse the data at 0.05 significant level. The result reveals that digital literacy plays a significant impact in the students’ educational research knowledge. The study among others concludes that acquisition of digital literacy skills should be made compulsory and mandatory for students seeking admission in tertiary institutions as its acquisition would go a long way to enhance their research knowledge.